Lost in the Lights : Sports, Dreams, and Life - Hemphill, Paul, 1936-2009 (Book collections on Project MUSE., 2003)
A veteran journalist's collection of sportswriting on the blue-collar South. Sport mirrors life. Or, in Paul Hemphill's opinion, 'Sport is life.' The 15 pieces in this compelling collection are arranged along the timeline for an aspiring athlete's dream: 'The Dawning, ' with stories about boys hoping and trying to become men, 'The Striving, ' about athletes at work, defining themselves through their play, and 'The Gloaming, ' about the twilight time when athletes contend with broken dreams and fading powers. Through all the pieces, Hemphill exhibits his passion for the sports he covers and a keen.